The effect of wet-grinding on coal mechanochemical pre-desulfurization. Issue 2 (1st June 2023) - Liu, Jinting; Zhao, Jing; Gu, Suqian; Fu, Xiaoheng
ABSTRACT: For reducing SOx emissions during industrial activities, a new desulfurization method is urgently needed to be exploited. Thus, a mechanochemical pre-desulfurization method was explored. For characterizing the change patterns of coal before and after grinding, N2 adsorption-desorption isotherms, X-ray diffraction (XRD), Fourier transform infrared spectroscopy (FTIR), and X-ray photoelectron spectroscopy (XPS) was utilized. The maximum% of desulfurization rate reached 24.69% under optimum conditions of wet-grinding, a 10% grinding concentration, and a period of grinding 90 min, at pH = 7. However, the desulfurization rate was almost zero by dry-grinding. The specific surface area of coal samples and its contents of FeSO4, and Fe2 (SO4 )3 changed from 3.570 m 2 ·g −1, 0.159%, and 0.593% of raw coal to 4.879 m 2 ·g −1, 0.611%, and 0.939% of the dry-grinding sample and 13.866 m 2 ·g −1, 0.939%, and 2.23% of the wet-grinding sample. The transformation from pyrite to soluble FeSO4 and Fe2 (SO4 )3 is the main reason for high-sulfur coal desulfurization during the process of wet-grinding. Therefore, this investigation puts forward a new and friendly desulfurization method for coal desulfurization.